Dynamic behaviours of reinforced concrete columns under cyclic loading with variable rates. Issue 4 (March 2020) - Xiao, SY; Li, JB; Mo, YL
The dynamic behaviour of reinforced concrete columns is inevitably affected by loading rate. This article reports the effect of loading rate on the dynamic behaviour of reinforced concrete columns under cyclic loading. Dynamic tests on reinforced concrete columns at five different loading rates were carried out using the MTS electro-hydraulic servo system. The cyclic loading was controlled by displacement with a loading rate ranging from 0.1 to 10 mm/s. Based on the test results, the effects of the loading rate on the hysteresis curves and the envelope curves of reinforced concrete columns were investigated. The research focused on the effect of loading rate on strength and deformation behaviour, including yielding and ultimate strengths as well as displacement. Finally, the effects of loading rate on the dissipated energy capabilities, the pinching effects and the stiffness degradation of reinforced concrete columns were also critically examined.